2019
DOI: 10.1111/modl.12592
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Unfocused Direct and Indirect Written Corrective Feedback on Rewritten Texts and New Texts: Looking into Feedback for Accuracy and Feedback for Acquisition

Abstract: This study attempts to add new empirical evidence on the language learning (operationalized and measured in terms of several dimensions of accuracy) that may derive from accessing and processing written corrective feedback (WCF) on one's own writing. The research questions examined potential interactions between type of WCF (direct vs. indirect), type of errors (grammar vs. nongrammar), and the perspective of feedback (accuracy vs. acquisition) in a single research design. To this end, 46 English majors at a S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
31
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(33 citation statements)
references
References 52 publications
(149 reference statements)
2
31
0
Order By: Relevance
“…Their finding reinforces the previous assumptions that indirect CF can be confusing (Suzuki, 2012). In contrast, direct feedback coupled with languaging can result in higher uptake, deeper processing, and more accuracy (Nicolás-Conesa et al, 2019). Comparing the relative effectiveness of self-languaging to a one-on-one conference with the teacher on L2 development, Boggs (2019) did not find any significant differences.…”
Section: Previous Studies On Wlsupporting
confidence: 83%
See 3 more Smart Citations
“…Their finding reinforces the previous assumptions that indirect CF can be confusing (Suzuki, 2012). In contrast, direct feedback coupled with languaging can result in higher uptake, deeper processing, and more accuracy (Nicolás-Conesa et al, 2019). Comparing the relative effectiveness of self-languaging to a one-on-one conference with the teacher on L2 development, Boggs (2019) did not find any significant differences.…”
Section: Previous Studies On Wlsupporting
confidence: 83%
“…Second, languaging can reveal if learners fail to grasp the nature of the problem despite receiving CF, and the iterative process makes it possible for the teacher to mediate further. Direct correction of errors does not guarantee understanding and learning, as indicated in the study by Nicolás-Conesa et al (2019) where the participants could successfully correct only half of their errors in the posttest. Without understanding the underlying reason for the CF, learners are less likely to learn (Ferris, 1995b;Suzuki, 2012).…”
Section: A Combination Of Languaging and Collaborative Dialogue In An Iterative Proceduresmentioning
confidence: 96%
See 2 more Smart Citations
“…Direct WCF provides the learner with a model of the correct L2 form, whereas indirect WCF offers the learner the opportunity to develop independence and problemsolving skills. Both Chandler (2003) and Nicolás-Conesa et al (2019), for example, reported the positive effects of direct WCF over the indirect form. Furthermore, a few studies (e.g., Bitchener & Knoch, 2010;Sheen et al, 2009) have examined the influence of direct WCF on the use of specific grammatical forms (e.g., articles, the copular verb be, past tense forms, and prepositions) and have reported noticeable linguistic gains.…”
Section: Previous Research On Wcfmentioning
confidence: 98%